Distributional Implications of Unemployment-Reducing Policies - Moutos, Thomas; Scarth, William (Journal of Income Distribution®, 2021)
We study the distributional implications that follow from the fact that higher-income households tend to consume higher-quality goods. This is done through a two-sector model in which one sector produces vertically differentiated products, whose skill intensity is an increasing function of quality. The skilled-to-unskilled wage ratio is fixed at a level sufficiently low that some unskilled workers remain unemployed. We show that uniform technological progress increases the unemployment rate, and we consider a number of policy responses to alleviate the “plight of the less-skilled”. Political economy consequences are emphasized, as we assess each policy’s chance of receiving political support. We conclude that a budget-neutral subsidy for the employment of unskilled workers is a viable policy option.